2021
DOI: 10.1038/s41597-021-01089-1
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific brain [18F]-FDG PET templates of Chinese subjects for statistical parametric mapping

Abstract: Statistical Parametric Mapping (SPM) is a computational approach for analysing functional brain images like Positron Emission Tomography (PET). When performing SPM analysis for different patient populations, brain PET template images representing population-specific brain morphometry and metabolism features are helpful. However, most currently available brain PET templates were constructed using the Caucasian data. To enrich the family of publicly available brain PET templates, we created Chinese-specific temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…reported that even with the use of individual MRI scans in the creation of the template, there is still a degree of distortion. Nevertheless, both studies demonstrated that the application of a local template provides better results when used in a non-Caucasian population 22 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…reported that even with the use of individual MRI scans in the creation of the template, there is still a degree of distortion. Nevertheless, both studies demonstrated that the application of a local template provides better results when used in a non-Caucasian population 22 …”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, both studies demonstrated that the application of a local template provides better results when used in a non-Caucasian population. 22 In our retrospective study, we only used subjects' PET images. The analysis workflow was predesigned, with the ability to be easily modified by the user, which is convenient and less time-consuming in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 169 patients (75 females; median [IQR] age, 58 [50–67] years) were introduced in this study. In addition, 116 normal brain 18 F-FDG PET images of healthy controls (39 females; median [IQR] age, 50 [41–60] years) were extracted from the open source image datasets ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…F-FDG PET images underwent spatial normalization using a population-specific brain 18 F-FDG PET template specifically tailored for Chinese subjects. 14 The Montreal Neurological Institute space served as the basis for this normalization process, using the symmetric diffeomorphic mapping algorithm in combination with advanced normalization tools. 15 A trilinear interpolation technique was applied to produce images composed of voxels measuring 2 Â 2 Â 2 mm.…”
mentioning
confidence: 99%